Book Notes [51, Spring 2003] - Finkel, Alvin (Labour/Le Travail, 2003)
The article briefly reviews Bridget Anderson's "Doing the Dirty Work? The Global Realities of Domestic Labour;" Barbara Paleczny's "Clothed in Integrity: Weaving Just Cultural Relations and the Garment Industry;" Walter Johnson's "Soul by Soul: Life Inside the Antebellum Slave Market;" Anna Heilman's "Never Far Away: The Auschwitz Chronicles of Anna Heilman;" Lesley Gill's "Teetering on the Rim: Global Restructuring, Daily Life, and the Armed Retreat of the Bolivian State;" "Public Sector Pay Determination in the European Union" edited by Robert Elliott, Claudio Lucifora, and Dominique Meurs; Philip Resnick's "The Politics of Resentment: British Columbia Regionalism and Canadian Unity;" "Against the Grain: Foresters and Politics in Nova Scotia" by L. Anders Sandberg and Peter Clancy; and "The Nonprofit Sector in Canada: Roles and Relationships," edited by Keith G. Banting.